SINEKTIKA DALAM AL-QUR’AN PERSPEKTIF MODEL PEMBELAJARAN: Studi Kasus Pendidikan Akidah-Akhlak (Karakter)Bagi Remaja - Maskur, Asep; Karimah, Ummah (Moderation | Journal of Islamic Studies Review, 2026)
This study aims to uncover the problems of Aqidah-Akhlak/character education (character building) and find alternative learning models as solutions. Facts in the field show that the character of adolescents is often problematic. Such conditions require appropriate solutions, one of which is through education. This study shows the existence of serious problems regarding character education caused by an inappropriate education system and learning patterns. Synectics in the Qur'an, the perspective of the learning model, offers an alternative learning approach constructed to increase spiritual, intellectual, emotional and social creativity. This improvement is carried out through a series of activities, in the form of optimizing the function of all potentials, especially hearing, sight and heart (intellect), by referring to the principles and instructions of the Qur'an. The implementation of this learning model is carried out using two strategies: First, combining each element that at first glance seems unrelated. Second, making analogies to find something or new meaning and making something unfamiliar become familiar. The results of this analysis are related to the discourse of the Synectics learning model designed by William J.J Gordon and the theory of Progressivism philosophy. John Dewey argued that: Progressivism is a forward-looking educational philosophy that positions students as subjects of education, equipped with the resources and potential to develop themselves and capable of resolving various problems they face. This philosophy holds that every human being, through their various experiences, always desires change, always develops, and becomes better. Synectics and Progressivism philosophy both emphasize that creativity is a crucial element in human development. Similarly, the interpretation of the verses of the Quran, particularly Surah Al-Nahl verse 78 and Surah Ali Imran verses 190 to 195 concerning the Ulu al-Albab (The Head of the Heart). As expressed in the views of Ibn Kathir, Sayyid Qutbh, and Quraish Shihab, the Ulu al-Albab (The Head of the Heart), with all its characteristics, is an inspiration for the ideal figure that should emerge as a product of an educational process.